2-Arachidonoylglycerol mobilizes myeloid cells and worsens heart function after acute myocardial infarction. Issue 3 (28th September 2018) - Schloss, Maximilian J; Horckmans, Michael; Guillamat-Prats, Raquel; Hering, Daniel; Lauer, Estelle; Lenglet, Sebastien; Weber, Christian; Thomas, Aurelien; Steffens, Sabine
Abstract: Aims: Myocardial infarction (MI) leads to an enhanced release of endocannabinoids and a massive accumulation of neutrophils and monocytes within the ischaemic myocardium. These myeloid cells originate from haematopoietic precursors in the bone marrow and are rapidly mobilized in response to MI. We aimed to determine whether endocannabinoid signalling is involved in myeloid cell mobilization and cardiac recruitment after ischaemia onset. Methods and results: Intravenous administration of endocannabinoid 2-arachidonoylglycerol (2-AG) into wild type (WT) C57BL6 mice induced a rapid increase of blood neutrophil and monocyte counts as measured by flow cytometry. This effect was blunted when using cannabinoid receptor 2 knockout mice. In response to MI induced in WT mice, the lipidomic analysis revealed significantly elevated plasma and cardiac levels of the endocannabinoid 2-AG 24 h after infarction, but no changes in anandamide, palmitoylethanolamide, and oleoylethanolamide. This was a consequence of an increased expression of 2-AG synthesizing enzyme diacylglycerol lipase and a decrease of metabolizing enzyme monoacylglycerol lipase (MAGL) in infarcted hearts, as determined by quantitative RT–PCR analysis. The opposite mRNA expression pattern was observed in bone marrow. Pharmacological blockade of MAGL with JZL184 and thus increased systemic 2-AG levels in WT mice subjected to MI resulted in elevated cardiac CXCL1, CXCL2, and MMP9 protein levels as well as higher cardiac neutrophil and monocyte counts 24 h after infarction compared with vehicle-treated mice. Increased post-MI inflammation in these mice led to an increased infarct size, an impaired ventricular scar formation assessed by histology and a worsened cardiac function in echocardiography evaluations up to 21 days. Likewise, JZL184-administration in a myocardial ischaemia-reperfusion model increased cardiac myeloid cell recruitment and resulted in a larger fibrotic scar size. Conclusion: These findings suggest that changes in endocannabinoid gradients due to altered tissue levels contribute to myeloid cell recruitment from the bone marrow to the infarcted heart, with crucial consequences on cardiac healing and function.